Predictive Value of Positive Margins in Diagnostic Biopsies of Dysplastic Nevi - Jeffrey S. Dickman; Reem M. Haddad; Andrew Racette (Hindawi Limited, 2020)
Dysplastic nevi (DN) are common and controversial and the best choice for management of DN after diagnosis is not always clear. The presence of positive margins found on diagnostic biopsy is used by many dermatologists when deciding whether to re-excise these lesions. In order to quantify the predictive value of positive margins in diagnostic biopsies of DN, we performed a review and analysis of the concordance between the histological findings of biopsies and their subsequent excisions. A total of 122 pathology reports from diagnostic biopsies of DN with nevus cells present at the tissue margin were reviewed. Within this sample, 68 total postbiopsy excisions had been performed. The excisional pathology reports were reviewed for the presence of residual or recurrent nevus cells. Residual nevus cells were reported in 29 of 63 available excisional pathology reports illustrating a positive predictive value (PPV) of positive margins in diagnostic biopsies of DN of 46.0%. We present this value along with PPVs from the very few existing similar studies. The quantified predictive value of positive margins in diagnostic biopsies is useful information for providers who must make decisions regarding the best treatment options for patients with DN. The low PPV of positive margins lends further evidence that DN of moderate severity or less may simply be monitored.